Institutional investors types and sustainability reporting: a study on Malaysian listed firms / Hafizah Abd-Mutalib, Che Zuriana Muhammad Jamil and Wan Nordin Wan-Hussin - Abd-Mutalib, Hafizah; Muhammad Jamil, Che Zuriana; Wan-Hussin, Wan Nordin (2013)
The purpose of this study is to examine if the investment styles of institutional investors in Malaysian listed firms are associated with the level of sustainability reporting. Based on a sample of 100 firms in 2009, the results indicate that the level of institutional shareholdings in aggregate has a positive association with the extent of sustainability reporting. However, when we dichotomized the institutional investors by their investment horizons, we find that the level of shareholdings by pension funds, which represents the long-term institutional investors, and the level of shareholding by short-term institutional investors, represented by the mutual funds and banks, are not linked to sustainability reporting.